The process of failing occupational therapy students: a staff perspective - Ilott, Irene (1993)
Assigning a fail grade, particularly when it results in the termination of a career goal, is a taboo and taken-for-granted aspect of an assessor's role. Hermeneutics provided the main framework for interpreting the subjective and objective experiences of both academic and fieldwork supervisors during this process.